Acute phase proteins as early biomarkers in buffaloes infected with Pasteurella multocida type B: 2 and its immunogens (LPS and OMP) - Lim, Eric Teik Chung; Abdullah, Faez Firdaus Jesse; Marza, Ali Dhiaa; Ibrahim, Hayder Hamzah; Saad, Mohd Zamri; Haron, Abd Wahid; Mohd Lila, Mohd Azmi; Saharee, Abdul Aziz (Faculty of Animal Husbandry, Brawijaya University, 2017)
Sudden death is usually the main finding in field animals during haemorrhagic septicaemia outbreaks in Malaysia due to the acute, fatal, and septicaemic disease of cattle and buffaloes. The aim of this study was to determine the acute phase responses in buffaloes infected with Pasteurella multocida type B: 2 and its immunogens lipopolysaccharide and outer membrane proteins. 21 buffalo heifers were divided into 7 treatment groups. Group 1 buffaloes were inoculated orally with 10 mL of sterile phosphate buffered saline (PBS) pH7 which act as negative control group. While Group 2 and 3 were inoculated subcutaneously and orally with 10 mL of 1012 colony forming unit (cfu) of Pasteurella multocida type B: 2 respectively. Group 4 and 5 buffaloes were inoculated with 10 mL of lipopolysaccharide broth intravenous and oral route respectively. Buffaloes in Group 6 and 7 were administered with 10 mL of outer membrane proteins broth subcutaneous and orally respectively. During the post infection period, all buffaloes were observed for clinical signs and clinical response for 21 days. Blood samples were also collected according to time interval for analyses of acute phase proteins concentration. All buffaloes from Group 1, 3, 4, 5, and 7 were able to survive throughout the stipulated experimental period of 21 days. Group 2 and 6 buffaloes were only able to survive for 12 hours and 3 days respectively. Buffaloes in all treatment groups of Pasteurella multocida type B: 2 and its immunogens lipopolysaccharide and outer membrane proteins showed significant increase in haptoglobin and serum amyloid A concentrations during early and late infection period respectively. There were significant different (p<0.05) in all treatment groups compared to control group. Buffaloes infected with Pasteurella multocida type B: 2 and its immunogens lipopolysaccharide and outer membrane proteins showed changes in both haptoglobin and serum amyloid A concentrations during the early and late infection period respectively. Information on this will play a significant role in understanding the acute phase response during haemorrhagic septicaemia outbreaks.